Stable Cycling of Fe2O3 Nanorice as an Anode through Electrochemical Porousness and the Solid-Electrolyte Interphase Thermolysis Approach - Liang, Jianwen; Wei, Denghu; Cheng, Qiushi; Zhu, Yongchun; Li, Xiaona; Fan, Long; Zhang, Jingjing; Qian, Yitai (ChemPlusChem (Weinheim, Germany), 2014)
A new thread for improving the cycling stability of Fe2O3 nanorice is proposed through combining the electrochemical porousness (EP) effect and solid–electrolyte interphase (SEI) thermolysis approach. Starting from solid Fe2O3 nanorice, this process could be applied to prepare porous Fe2O3 nanorice with a good coating of a porous SEI thermolysis layer composed of carbon and Li2O. The interconnecting pores and full coating of the SEI thermolysis layer provides not only mechanical resistance of the Fe2O3 nanorice against pulverization, but also high electrical and ionic conductivity over the electrode throughout long cell cycles. This method results in the enhancement of cycling ability and capacity, which is demonstrated by comparison with the starting Fe2O3 nanorice. After the EP and SEI thermolysis approach, the Fe2O3 nanorice exhibits an energy capacity retention about of 680 mAh g−1 at a current density of 1000 mA g−1 over 250 cycles, which is more than 82 % of the initial reversible capacity. Moreover, it also has an excellent rate capability and high coulombic efficiency. This strategy provides a simple and convenient route toward stable charge/discharge cycling for not only Fe2O3, but also for other electrode materials that are subject to large volume changes and low charge voltages. At the same time, it also contributes to a fundamental understanding of improved cycling stability and reversible capacity for electrode materials. Hollow grains: A new method for improving the cycling stability of Fe2O3 nanorice by combining electrochemical porousness and the solid–electrolyte interphase (SEI) layer thermolysis approach is proposed (see picture). This process can be applied to prepare porous Fe2O3 and enables coating of a porous SEI thermolysis layer on the surface of Fe2O3, leading to remarkable lithium storage performance.